2021
DOI: 10.1134/s1075700721040109
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Forecast of the Poverty Rate in the Arctic Zone of the Republic of Sakha (Yakutia)

Abstract: — The article analyzes the indicators of the poverty level in the regions of the Arctic zone of the Russian Federation, and assesses the level of poverty and quality of life in the Arctic zone of Yakutia. The results of sociological studies on the level of poverty in the Arctic regions are presented as well as the measures for its reduction associated with addressing the problems of employment, increasing incomes of the population, and the development of traditional crafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…This type of assessment is critical for understanding the sources of social tension and the administration of government programs for the poor. The use of this approach allows for the selection of the more significant aspects of poverty, as it manifests itself not only in insufficient livelihoods but also in health, nutrition, education, housing conditions, and social isolation (Markova, 2021). Poverty reduction in developing regions is slowing due to the prevalence of extreme income inequality, which is regarded as a significant threat to economic progress.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…This type of assessment is critical for understanding the sources of social tension and the administration of government programs for the poor. The use of this approach allows for the selection of the more significant aspects of poverty, as it manifests itself not only in insufficient livelihoods but also in health, nutrition, education, housing conditions, and social isolation (Markova, 2021). Poverty reduction in developing regions is slowing due to the prevalence of extreme income inequality, which is regarded as a significant threat to economic progress.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…[3] in Ukraine poverty is caused by unequal distribution. [4] in the Arctic of the Russian Federation, the solution to overcoming poverty through employment and increasing the income of the population. [5] overcoming poverty through Business, Entrepreneurship, and Innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the distinct challenges the Arctic faces in relation to the COVID-19 pandemic and potentially similar public health or infectious disease emergencies. Markova et al 37 , Lemieux et al 38 , Simonen et al 39 , Cook & Johannsdottir [ 40 ], Men & Tarasuk 41 , and Golubeva et al 42 ,all have pointed out that the COVID-19 pandemic has exacerbated the existing socioeconomic vulnerability, food insecurity and health outcomes of the Arctic residents. The pandemic has pushed the people of Sakha (Northeastern Siberia, Russia) into poverty as people have lost their jobs and lacked stable earnings (overdue wage arrears) [ 37 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Markova et al 37 , Lemieux et al 38 , Simonen et al 39 , Cook & Johannsdottir [ 40 ], Men & Tarasuk 41 , and Golubeva et al 42 ,all have pointed out that the COVID-19 pandemic has exacerbated the existing socioeconomic vulnerability, food insecurity and health outcomes of the Arctic residents. The pandemic has pushed the people of Sakha (Northeastern Siberia, Russia) into poverty as people have lost their jobs and lacked stable earnings (overdue wage arrears) [ 37 , 43 ]. The pandemic has exacerbated the skilled workforce shortage in Northern Finland, Sweden, and Norway, especially in the five Arctic communities (i.e.…”
Section: Introductionmentioning
confidence: 99%